IMPLEMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE TPS (THINK PAIR SHARE) DALAM MENINGKATKAN KECERDASAN INTERPERSONAL SISWA PADA MATA PELAJARAN PAI (Studi Deskriptif Kualitatif di SMPN 02 Cibitung) - Nurlaelatul Maulidiyah; Wisnawati Loes (Program Studi Pendidikan Agama Islam, Fakultas Agama Islam UNISMA Bekasi, 2020)
Innovative learning that can develop social attitudes and communication skills, activeness,and the process of interaction between individuals that can be used as a means of social interactionbetween students and at the same time answer problems that exist in school, then the use of this TPS(Think Pair Share) type of cooperative learning strategy effective enough to overcome the problemsof students who are lacking in socializing and are less able to express their opinions to their friends.This study describes the implementation of the TPS (Think Pair Share) Cooperative Learning Modelin Improving Students’ Interpersonal Intelligence in PAI Subjects at SMPN 02 Cibitung. The results ofthe study explain that the implementation of the TPS (Think Pair Share) Cooperative Learning Modelat SMPN 02 Cibitung can be said to be running well in accordance with the theory and steps of theTPS (Think Pair Share) Cooperative Learning Model. With the TPS (Think Pair Share) CooperativeLearning Model, students’ interpersonal intelligence in PAI subjects increases, among others: 1.students have a sense of empathy for their friends 2. students like to interact with their friends well3. students prefer to work in groups 4. students can communicate actively and well as well as thesocial spirit of students, especially in PAI subjects. Compared to using other methods, although in itsimplementation there are obstacles faced, one of which is the lack of infrastructure in learning such asthe lack of LCDs and classes without air conditioning.